2022
DOI: 10.2147/jpr.s385910
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Pain Sensitization Associated with Response to Exercise Therapy in Patients with Knee Osteoarthritis: A Prospective Cohort Study

Abstract: Knee osteoarthritis (KOA) is a degenerative disease with inflammation, becoming persistent as it progresses, resulting in reduced quality of life. Exercise is the recommended treatment for KOA; however, the extent of pain reduction with exercise is heterogeneous and the prognostic implications of baseline factors in patients undergoing exercise are still unknown. This study examined the association between the response to exercise therapy and clinical outcomes, radiologic severity, and pain sensitization, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…In examining baseline pain sensitivity factors that may be associated with response to each intervention, significant correlations were not observed with the exception of a significant, positive moderate association with baseline heat pain threshold applied over the trapezius (r = 0.61, p<0.01) and temporal summation (r = 0.46, p = 0.04) with EIH during low intensity exercise. Temporal summation has been previously associated with response to exercise[ 7 , 8 ]. However, our study demonstrated this measure is also associated with response to low intensity dynamic resistance exercise in healthy individuals which contributes to the literature in a novel way and expands our broader understanding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In examining baseline pain sensitivity factors that may be associated with response to each intervention, significant correlations were not observed with the exception of a significant, positive moderate association with baseline heat pain threshold applied over the trapezius (r = 0.61, p<0.01) and temporal summation (r = 0.46, p = 0.04) with EIH during low intensity exercise. Temporal summation has been previously associated with response to exercise[ 7 , 8 ]. However, our study demonstrated this measure is also associated with response to low intensity dynamic resistance exercise in healthy individuals which contributes to the literature in a novel way and expands our broader understanding.…”
Section: Discussionmentioning
confidence: 99%
“…It remains unclear why certain individuals demonstrate hyperalgesia in response to exercise; [ 1 , 2 ] however, pain sensitization may be a contributing factor. Significantly higher temporal summation and lower pressure pain threshold at multiple locations have been demonstrated in individuals who are considered ‘non-responders’ to a twelve week aerobic and strength training in patients with knee osteoarthritis [ 7 ] . Temporal summation is also predictive of individuals who display an increase in clinical pain during exercise [ 8 ] .…”
Section: Introductionmentioning
confidence: 99%
“…2) 22 . The PPT at the knee was de ned as the lowest PPT at the four sites 23 . The mean of the two measurements was used for the analysis.…”
Section: Pain Sensitizationmentioning
confidence: 99%
“…Subsequently, ten sequential stimuli were applied to the same site in 1-second intervals, and the patients reported the pain intensity for the last stimulation on the VAS. The TSP value was calculated as the difference between the 10th VAS score and the rst VAS score 23 . The pressure intensity of the sequential stimuli was equal to the PPT level.…”
Section: Pain Sensitizationmentioning
confidence: 99%
“…3,11,43 Pain sensitization is a factor that decreases treatment response to exercise therapy and pharmacotherapy. 10,15,16 Moreover, alterations in the central nervous system may cause various symptoms, such as fatigue and poor sleep, which are called central sensitization-related symptoms and affect KOA pain symptoms. 2,15 Thus, factors contributing to pain symptoms are varied, but which ones are strongly associated with MEP in KOA remains unclear.…”
Section: Introductionmentioning
confidence: 99%